Peripherally Inserted Central Venous Catheters (PICC) versus totally implantable venous access device (PORT) for chemotherapy administration: a meta-analysis on gynecological cancer patients - Capozzi, Vito Andrea; Monfardini, Luciano; Sozzi, Giulio; Armano, Giulia; Butera, Diana; Scarpelli, Elisa; Barresi, Giuseppe; Benegiamo, Alessandro; Berretta, Roberto (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Ninety-four thousand gynecological cancer diagnoses are performed each year in the United States. The majority of these tumors require systemic adjuvant therapy. Sustained venous access was overcome by indwelling long-term central venous catheter (CVC). The best choice of which CVC to use is often arbitrary or dependent on physician confidence. This meta-analysis aims to compare PORT and peripherally inserted central catheter (PICC) outcomes during adjuvant treatment for gynecological cancer.Methods: Meta-analysis Of Observational Studies in Epidemiology (MOOSE) and the preferred reporting items for systematic reviews and meta-analyses statement (PRISMA)were used to conduct the meta-analysis.Results: 1320 patients were included, 794 belonging to the PORT group and 526 to the PICC group. Total complication rates were fewer in the PORT group, p = 0.05. CVC malfunction was less frequent in the PORT group than in the PICC group, p